On some new steiner 2-designs 5(2,5,45) - Crnković, Dean; Danilović, Doris Dumicić; Rukavina, Sanja; Šimac, Marina (Utilitas Mathematica, 2019)
In this paper we classify Steiner 5(2,5,45) designs having an automorphism group isomorphic to Ze or Eg. We also construct 5(2, 5,45) designs having 53 as an automorphism group. Among the con-structed Steiner designs there are 12 mutually nonisomorphic ones. To our best knowledge, 11 of the constructed Steiner 5(2,5,45) designs are new. We also study LDPC codes of Steiner 5(2,5,45) designs. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.